Sistem Informasi Reservasi Pada Rumah Makan Dapur Pindang Komering - M. Wahyu Juliansa; Edi Supratman (Jurnal Ilmiah Matrik, 2025)
Pindang Komering is a traditional dish from the Komering region in South Sumatra, well known for its delicious taste. Dapur Pindang Komering restaurant offers a solution for traditional Palembang cuisine in the digital era. Located at Jalan Bungaran No.2, 7 Ulu, Palembang City, the restaurant currently relies on reservations made by phone or in person. This often leads to customer congestion during peak hours and limits access to menu information when booking. To address these issues, a website-based reservation system is needed, allowing customers to make reservations, view the menu, order food, and make payments online—anytime and anywhere. Customers simply need to show proof of reservation upon arrival. The system is developed using the Waterfall method, a linear and structured software development approach where each phase must be completed before moving to the next. This reservation system is expected to make the process of booking, ordering, and payment more effective and efficient, while also enhancing the overall service quality of Dapur Pindang Komering restaurant.